Characterization of PD-1 and PD-L1 expression in papillary renal cell carcinoma: results of a large multicenter study - Erlmeier, Franziska; Steffens, Sandra; Stöhr, Christine; Herrmann, Edwin; Polifka, Iris; Agaimy, Abbas; Trojan, Lutz; Ströbel, Philipp; Becker, Frank; Wülfing, Christian; Barth, Peter; Stöckle, Michael; et al. (Clinical genitourinary cancer, 2021)
Background - Programmed cell death protein 1 (PD-1)/programmed death-ligand 1 (PD-L1) play a decisive role as prognostic markers in clear-cell renal cell carcinoma (RCC). To date, the role of PD-1/PD-L1 as a prognostic marker in papillary RCC (pRCC) remains scarce. - Patients and Methods - Patients’ sample collection was a joint collaboration of the nationwide PANZAR consortium - a multicenter study. Medical history and tumor specimens were collected from 245 and 129 patients with pRCC types 1 and 2, respectively. Expression of PD-1 and PD-L1 was determined by immunohistochemistry in pRCC and tumor-infiltrating mononuclear cells. - Results - Of 374 pRCC specimens, 204 type 1 and 97 type 2 were evaluable for PD-1 and PD-L1 expression analysis. In total, PD-1 and PD-L1 expression were found in 8 (4.9%) of 162 and 12 (7.2%) of 166 evaluable pRCC type 1 specimens. Comparably, PD-1 and PD-L1 expression were found in 2 (2.4%) of 83 and 5 (6.2%) of 81 evaluable pRCC type 2 specimens. Hardly any clinically relevant associations between PD-1 and PD-L1 positivity and clinicopathologic or clinical courses were observed, neither in pRCC type 1 nor type 2. - Conclusion - The analysis of a large pRCC cohort from a multicenter consortium revealed no impact of PD-1/PD-L1 expression on prognosis in patients with pRCC with predominantly limited disease status, neither for type 1 nor type 2. However, the impact of PD-1 and PD-L1 in more advanced pRCC disease needs further elucidation.
Epub: Jul 9, 2020
Gesehen am 13.07.2021